2015
DOI: 10.1139/apnm-2015-0184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation-induced resistance exercise on mitochondrial fission and fusion proteins in rat skeletal muscle

Abstract: It is well known that resistance exercise increases muscle protein synthesis and muscle strength. However, little is known about the effect of resistance exercise on mitochondrial dynamics, which is coupled with mitochondrial function. In skeletal muscle, mitochondria exist as dynamic networks that are continuously remodeling through fusion and fission. The purpose of this study was to investigate the effect of acute and chronic resistance exercise, which induces muscle hypertrophy, on the expression of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 40 publications
6
43
0
Order By: Relevance
“…These protein levels also associated with alteration in muscle fiber composition. Denervation decreases mitochondrial volume with down‐regulation of mitochondrial fusion proteins Opa1 and Mfn2 (Iqbal et al, ; Kitaoka et al, ), whereas chronic contractile activity leads to reticular mitochondria with up‐regulation of these proteins (Iqbal et al, ; Kitaoka et al, ). These findings suggest that slow‐to‐fast fiber type transition decreased mitochondrial volume and dynamics protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…These protein levels also associated with alteration in muscle fiber composition. Denervation decreases mitochondrial volume with down‐regulation of mitochondrial fusion proteins Opa1 and Mfn2 (Iqbal et al, ; Kitaoka et al, ), whereas chronic contractile activity leads to reticular mitochondria with up‐regulation of these proteins (Iqbal et al, ; Kitaoka et al, ). These findings suggest that slow‐to‐fast fiber type transition decreased mitochondrial volume and dynamics protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have shown an increased abundance of autophagy proteins including Drp1 and Bcl-2 and 19 kDa interacting protein-3 (Bnip3) after exercise (60, 65, 71, 78). Bnip3 functions as a mitophagy receptor to recruit selected autophagosomes for elimination.…”
Section: Foxo Proteins and The Ubiquitin Proteasome System (Ups) In Mmentioning
confidence: 99%
“…In line with this, during acute endurance exercise, mRNA levels of MFN1 and MFN2 (markers of mitochondrial fusion) were increased at 12 and 24 h after exercise in humans and rats, partly mediated by the PGC1α/ERRα pathway (Cartoni et al, ; Ding et al, ). In addition, MFN1, MFN2, and OPA1 protein levels were elevated 24 and 48 h after long‐term resistance or endurance exercise training in the rats and mice skeletal muscle (Greene et al, ; Ju et al, ; Kitaoka, Ogasawara, Tamura, Fujita, & Hatta, ). However, the above mitochondrial fusion markers seemed to have no change or decreased expression immediately and 1 h after exercise (Bori et al, ; Cartoni et al, ; Ding et al, ; Jamart, Naslain, Gilson, & Francaux, ; Kitaoka et al, ).…”
Section: Mitochondrial Adaptation To Exercisementioning
confidence: 99%
“…In addition, MFN1, MFN2, and OPA1 protein levels were elevated 24 and 48 h after long‐term resistance or endurance exercise training in the rats and mice skeletal muscle (Greene et al, ; Ju et al, ; Kitaoka, Ogasawara, Tamura, Fujita, & Hatta, ). However, the above mitochondrial fusion markers seemed to have no change or decreased expression immediately and 1 h after exercise (Bori et al, ; Cartoni et al, ; Ding et al, ; Jamart, Naslain, Gilson, & Francaux, ; Kitaoka et al, ). Therefore, mitochondrial fusion in the skeletal muscle may depend on timepoints of exercise.…”
Section: Mitochondrial Adaptation To Exercisementioning
confidence: 99%
See 1 more Smart Citation